Digital rectal examination is not a useful screening test for prostate cancer - Krilaviciute, Agne; Becker, Nikolaus; Lakes, Jale; Radtke, Jan Philipp; Kuczyk, Markus; Peters, Inga; Harke, Nina N.; Debus, Jürgen; Körber, Stefan A.; Herkommer, Kathleen; Gschwend, Jürgen E.; Meissner, Valentin H.; et al. (European urology oncology, 2023)
Background - Annual digital rectal examination (DRE) is recommended as a stand-alone screening test for prostate cancer (PCa) in Germany for 45+ yr olds. DRE diagnostic performance in men as young as 45 yr old has not been proved by a screening trial. - Objective - To determine DRE diagnostic performance in a screening trial. - Design, setting, and participants - This analysis was conducted within the multicentric, randomized PROBASE trial, which enrolled >46 000 men at age 45 to test risk-adapted prostate-specific antigen (PSA) screening for PCa. - Intervention - (1) DRE was analyzed as a one-time, stand-alone screening offer at age 45 in 6537 men in one arm of the trial and (2) PCa detection by DRE was evaluated at the time of PSA-screen-driven biopsies (N = 578). - Outcome measurements and statistical analysis - (1) True-/false-positive detection rates of DRE as compared with PSA screening and (2) DRE outcome at the time of a prostate biopsy were evaluated. - Results and limitations - (1) A prospective analysis of 57 men with suspicious DRE at age 45 revealed three PCa. Detection rate by DRE was 0.05% (three of 6537) as compared with a four-fold higher rate by PSA screening (48 of 23 301, 0.21%). The true-positive detection rate by DRE relative to screening by PSA was 0.22 (95% confidence interval [CI] = [0.07-0.72]) and the false-positive detection rate by DRE was 2.2 (95% CI = [1.50-3.17]). (2) Among PSA-screen-detected PCa cases, 86% had unsuspicious DRE (sensitivity relative to PSA was 14%), with the majority of these tumors (86%) located in the potentially accessible zones of the prostate as seen by magnetic resonance imaging. - Conclusions - The performance of stand-alone DRE to screen for PCa is poor. DRE should not be recommended as a PCa screening test in young men. Furthermore, DRE does not improve the detection of PSA-screen-detected PCa. - Patient summary - Our report demonstrated the poor diagnostic performance of digital rectal examination in the screening for prostate cancer in young men.